KORELASI ANTARA MAKNA SITUS SEJARAH DENGAN SENSE OF PLACE - Atie Ernawati (Lakar: Jurnal Arsitektur, 2021)
Preservation efforts The pilgrimage site area which has a fairly strong historical value is mostly done through physical approaches and visual approaches such as restoration, conservation, preservation and others. In this study, researchers attempted to conduct a study with a non-physical approach as one of the conservation efforts by conducting a correlation analysis between the meaning of pilgrimage sites with a sense of place. With a quantitative approach, the analysis process is carried out through two stages, the first stage is the analysis of content from questionnaires, analysis of open codings, axial coding to selective coding. The next stage is factor analysis and correlation analysis. Based on the results of correlation analysis, the results show that religious meanings have a strong relationship with sense of belonging in the sense of place category with a correlation coefficient of 0.64, while the socio-cultural meaning has a moderate correlation with the correlation coefficient of 0.18. Conversely, pilgrims who have negative meanings have a high correlation with unbound feeling with a coefficient of 0.52. Through this research, it is expected that a behavioral-based approach can be carried out as one of the efforts to preserve the area of the pilgrimage site.